Neuropathology and apolipoprotein E profile of aged chimpanzees: implications for Alzheimer disease. - Gearing, M (1994)
Neuropathological findings in three aged chimpanzees were compared with those in rhesus monkeys and individuals with Alzheimer disease. Senile plaques and blood vessels were immunoreactive for amyloid beta-protein and apolipoprotein E (apoE) in the nonhuman primates, recapitulating findings in human aging and Alzheimer disease. Neurofibrillary tangles, another hallmark of Alzheimer disease, were absent. PCR/restriction-enzyme analysis in chimpanzees revealed an APOE profile similar to the human APOE type 4 allele associated with an increased risk of Alzheimer disease. These findings militate against the hypothesis that the absence of APOE type 3 allele predisposes to neurofibrillary tangle formation and support the value of aged primates for exploring mechanisms of amyloid processing and the role of apoE.